Features of development of speed force for the schoolchildren of junior classes - Худолій, О. М.; Іващенко, О. В.; Мірошниченко, Д. Т. (Physical Education Theory and Methodology, 2012)
The article is sanctified to perfection of methodology of development of speed force for the schoolchildren of junior classes. Power office hours that assist a positive dynamics in development of speed force are examined. On the basis of data of experiment there is the set efficiency of an offer methodology, worked out scale of estimation of level of development of speed force.